PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN BERBASIS KINERJA DAN JOB RELEVANT INFORMASI TERHADAP KINERJA 15 SKPD DI KABUPATEN KUNINGAN - Mardiyani, Mardiyani (Jurnal Manajemen Magister Darmajaya, 2016)
This research as a purpose to the test influence participation in performance based budgeting and job relevant information toward managerial performance at 15 SKPD Kuningan regency. The methodologies of Reseach issurvey-explanatory.Sampling used was 15 SKPD Kuningan regency. Analysis technique used path analysis wit Lisrel Program.The Result of data analysis show thatparticipation in performance based budgeting have a significant effect to manajerial performancewhich mean if the higherparticipation in performance based budgeting will cause performanceimprovement at 15 SKPD kuningan regency, while participation in performance based budgeting have no significant effect to job relevant informationwhich mean if the participation of performance based budgeting is not supported by the human resources that understand the ability of budget preparation will result in the job relevant information decreased because the information obtainedless accurate. While job relevant informationhave no significant effect tomanagerial performance increased which mean that the job relevant information less accurate will cause the performance is not maximal at 15 SKPD Kuningan regency.Â Keywords:Â  Participation in Performance Based Budgeting, Job Relevant Information, Managerial Performance